2004
DOI: 10.1111/j.1398-9995.2003.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory allergy in apprentice bakers: do occupational allergies follow the allergic march?

Abstract: The incidence of occupational asthma and rhinitis in apprentice bakers is high and increases z with the duration of exposure. Skin reactivity to common and occupational allergens is the main risk factor of bakers' asthma. Most cases of work-related respiratory symptoms among apprentice bakers are related to a specific sensitization. In most subjects who developed occupational asthma, rhinitis occurred at the same time as the chest symptoms did.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
2
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 27 publications
7
79
2
9
Order By: Relevance
“…A previous longitudinal study 33 indicated that the incidence of positive SPT to occupational allergens in apprentice bakers increases with the duration of exposure and that positive SPT to occupational allergens at the commencement of training was a significant risk factor for asthma. Further longitudinal genetic studies are required to elucidate the genetic effects of TLR4 on allergic sensitization to new allergen exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A previous longitudinal study 33 indicated that the incidence of positive SPT to occupational allergens in apprentice bakers increases with the duration of exposure and that positive SPT to occupational allergens at the commencement of training was a significant risk factor for asthma. Further longitudinal genetic studies are required to elucidate the genetic effects of TLR4 on allergic sensitization to new allergen exposure.…”
Section: Discussionmentioning
confidence: 99%
“…To date, results from general population studies were based on surveillance schemes and national disease registers. High-risk workforce cohort studies comprise a few recently published studies among apprentices [5][6][7][8] and newly hired workers [9], designed to reduce the selection biases in those cohorts. Both showed high incidences of work-related rhinitis and asthma, with very short latency periods, especially for rhinitis.…”
mentioning
confidence: 99%
“…apprentice pastry makers, bakery workers and workers exposed to laboratory animals) and, thus, in contrast to our study, did not include an unexposed reference group [10,11,34]. However, having such a group is crucial in estimating the excess risk that is attributable to a certain exposure compared to the background risk in the population without that exposure.…”
Section: Strengths and Limitationsmentioning
confidence: 76%
“…Most studies on the incidence of asthma and allergies during the first years of work life were performed in occupational cohorts, e.g. bakery apprentices [10,11]. In one of the few population-based studies assessing risk of occupational exposure, the ECRHS (European Community Respiratory Health Survey) [12], an increased risk was seen for asthma [13], but not for allergic rhinitis [14].…”
Section: Introductionmentioning
confidence: 99%